Evidence-based tailored nutrition educational intervention improves adherence to dietary guidelines, anthropometric measures and serum metabolic biomarkers in early-stage breast cancer patients: A prospective interventional study. (December 2021) - Trestini, Ilaria; Sperduti, Isabella; Caldart, Alberto; Bonaiuto, Clelia; Fiorio, Elena; Parolin, Veronica; Zambonin, Valentina; Zanelli, Sara; Tregnago, Daniela; Avancini, Alice; Cintoni, Marco; Pilotto, Sara; et al.
Abstract: Purpose: The impact of the adherence to dietary guidelines of early-stage breast cancer (EBC) patients on body composition changes during treatment is not entirely defined. This study aimed to evaluate the role of an evidence-based nutrition educational intervention, according to adherence to dietary guidelines, in EBC patients. Methods: This prospective study included EBC patients, candidates for neoadjuvant/adjuvant therapy. Patients received an evidence-based tailored nutrition educational intervention. The adherence to dietary guidelines, anthropometric and dietary assessments, and blood glucose and lipid profile tests were evaluated at baseline and after a 12-months nutritional intervention. Results: Two hundred and forty-three patients were enrolled. At baseline, 38.3% and 23.9% of patients were overweight and obese, weight gain ≥5% (compared to 6-months before enrollment) and central obesity were observed in 47.3% and 52.7% of patients, respectively. Adherence to dietary guidelines was low (median Med-Diet score: 6 [IQR 4–8]). After the nutritional intervention (median follow-up: 22 months [range 12–45]), adherence to dietary guidelines significantly increased (median Med-Diet score: 12 [IQR 8–13]), p < 0.0001 ). High adherence to dietary guidelines (defines as Med-Diet score ≥10) significantly correlated with: 1) overall weight loss ≥5% (21.8% vs. 2.5%, p  =  0.003 ); 2) median BMI drop (from 25.6 kg/m 2 to 24.4 kg/m 2, p  =  0.003 ); 3) lower prevalence of central obesity (38.2% vs. 7.2%, p  =  0.01 ); 4) improvement in blood glucose levels and lipid profile. Conclusion: This study suggests that an evidence-based tailored nutrition educational intervention during treatment for EBC significantly increases overall adherence to dietary guidelines, and it improves both anthropometric measures and serum metabolic biomarkers in patients with high adherence. Highlights: A nutritional intervention improves adherence to dietary guidelines among patients with early-stage breast cancer. High adherence to dietary guidelines enhances anthropometric measures. Serum metabolic profile improves with high adherence to dietary guidelines. Early-stage breast cancer patients should receive a nutritional assessment immediately after diagnosis. Dietary intervention, to control body weight, could enhance the disease outcome.